The influence of drinking tubewell water on diarrhea rates in Matlab Thana, Bangladesh - Curlin, George T. (Working paper (Cholera Research Laboratory), 1977)
Report of a 1974-1975 survey in twelve selected villages in Matlab Thana, Comilla District, Bangladesh.